Lessons on collisionless reconnection from quantum fluids - Narita, Yasuhito; Baumjohann, Wolfgang (Frontiers in Physics, 2014)
Magnetic reconnection in space plasmas remains a challenge in physics in that the phenomenon is associated with the breakdown of frozen-in magnetic field in a collisionless medium. Such a topology change can also be found in superfluidity, known as the quantum vortex reconnection. We give a plasma physicists' view of superfluidity to obtain insights on essential processes in collisionless reconnection, including discussion of the kinetic and fluid pictures, wave dynamics, and time reversal asymmetry. The most important lesson from the quantum fluid is the scenario that reconnection is controlled by the physics of topological defects on the microscopic scale, and by the physics of turbulence on the macroscopic scale. Quantum vortex reconnection is accompanied by wave emission in the form of Kelvin waves and sound waves, which imprints the time reversal asymmetry.